Dynamic Simulation Model for Predicting the Value of Health Degradation that Caused by Air Pollution of the NO2 Gas - Listyarini, Sri; ., . (International Journal of Engineering and Technology, 2018)
In Jakarta the majority of energy comes from fossil fuel burning, which also emitting the NO2 gas as air pollution. NO2 gas that inhaled by humans will damage the respiratory system called Respiratory Symptomps Disease (RSD). This research aims to predict the value of health degradation which comes from NO2 gas air pollution by developing a dynamic simulation model. When the ambient concentration of NO2 gas exceeds the standard, some of Jakarta residents will get RSD. The value that has to be paid by Jakarta residents who will get this disease is predicted by the dynamic simulation model. The result of this research is that started the year 2018 there will be 973 Jakarta residents who have RSD from NO2 air pollution gas and will continue to increase until 109,263 in 2025. In 2025 the citizens of Jakarta which will be get RSD caused by NO2 gas as air pollution will have to pay approximately US 30.5 M, or about 12.5 percent of the GDRP.